2018
DOI: 10.1186/s12916-018-1053-3
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment chest x-ray severity and its relation to bacterial burden in smear positive pulmonary tuberculosis

Abstract: BackgroundChest radiographs are used for diagnosis and severity assessment in tuberculosis (TB). The extent of disease as determined by smear grade and cavitation as a binary measure can predict 2-month smear results, but little has been done to determine whether radiological severity reflects the bacterial burden at diagnosis.MethodsPre-treatment chest x-rays from 1837 participants with smear-positive pulmonary TB enrolled into the REMoxTB trial (Gillespie et al., N Engl J Med 371:1577–87, 2014) were retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
23
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 36 publications
9
23
1
3
Order By: Relevance
“…Furthermore, in multivariate analysis of independent associated indices for lung lesions, higher sputum bacterial counts are associated with cavitation, but not vice versa. Our result is consistent with a recent report that in those cases without cavitation, the radiological severity of disease on chest X-ray prior to treatment in smear-positive pulmonary TB patients has no association with the bacterial burden [ 40 ]. It may therefore explain the seemingly paradox association of BMI [ 41 43 ] and anti-TB antibody [ 26 , 44 , 45 ] response with the bacterial counts and cavity in TB patients, in our data and previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, in multivariate analysis of independent associated indices for lung lesions, higher sputum bacterial counts are associated with cavitation, but not vice versa. Our result is consistent with a recent report that in those cases without cavitation, the radiological severity of disease on chest X-ray prior to treatment in smear-positive pulmonary TB patients has no association with the bacterial burden [ 40 ]. It may therefore explain the seemingly paradox association of BMI [ 41 43 ] and anti-TB antibody [ 26 , 44 , 45 ] response with the bacterial counts and cavity in TB patients, in our data and previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, a significant positive correlation between Rv3737 expression level and bacterial load in pulmonary TB patients raises the possibility that the isolates with increased expression of Rv3737 are prone to escaping clearance by alveolar macrophages, thus leading to greater bacillary multiplication in host. The high bacterial burden always causes more lung damage and higher mortality [24,25]. In line with previous observation, we observed that the higher expression of Rv3737 was more likely to result in more cavities among patients affected by pulmonary TB.…”
Section: Discussionsupporting
confidence: 90%
“…Whereas, in a study conducted by Murthy et al ., reported that the radiological severity of disease on chest X-ray prior to treatment in smear positive pulmonary TB patients was weakly associated with the bacterial burden. 24 In our study, bilateral lesions were significantly more predominant among PTB patients with diabetes mellitus (69.7%) (Table 4). Also, majority of PTB patients with DM (38.5%) had high bacillary load of 3+.…”
Section: Discussionsupporting
confidence: 55%